Tau Propagation as a Diagnostic and Therapeutic Target for Dementia: Potentials and Unanswered Questions - Takeda, Shuko (Frontiers in Neuroscience, 2019)
A unique clinical course of Alzheimer’s disease (AD), beginning with memory deficit as the earliest symptom, is well-correlated with a progressive pattern of intracellular aggregates of tau (neurofibrillary tangles), which spread from the medial temporal lobe to other brain areas in a stereotypical manner. Recent findings from basic research using in vitro and in vivo models demonstrated that pathological forms of extracellular tau can be taken up by cells and induce intracellular tau aggregates. On the basis of these neuropathological observations and experimental findings, the “tau propagation hypothesis” has been proposed, in which the stereotypical spreading of the tau pathology observed in the brain of AD patients can be explained by the interneuron transfer of the pathological form of tau. The concept of tau propagation remains controversial, and many unsolved questions exist; however, it has been attracting attention as a potential therapeutic target for halting AD progression. This article reviews the recent findings regarding the tau propagation hypothesis, including the basic concept and evidence of interneuron tau transfer, potentials as a diagnostic and therapeutic target, and unsolved questions for a better understanding of tau propagation.